L’intelligenza artificiale nei servizi sociali e sanitari: una nuova sfida al ruolo delle istituzioni pubbliche nel welfare italiano? (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The paper illustrates the applications of digital and artificial intelligence technologies in social and health services and emphasizes the need of careful regulation by public authorities to ensure equality and constitutional rights.
Keywords: artificial intelligence; digital technologies; social and health services; constitutional principles; regulation